Firm-Specific Determinants of the Real Wage - Currie, Janet; McConnell, Sheena (The Review of Economics and Statistics, 1992)
Bargaining models suggest that firm-specific variables play an important role in wage determination. Yet previous empirical studies of wage determination have largely ignored these variables. Our analysis of a large panel data set of U.S. wage contracts suggests that firm-specific variables suggested by bargaining models. such as the values of sales. the capital-labor ratio, and the financial liquidity of the firm. are important determinants of negotiated real wages.